Advancing equity in STEM education for girls in sub-Saharan Africa: A systematic review through an intersectional lens - Ojong, Akem Solange; Kareem, Edouard (American Journal of STEM Education, 2025)
Persistent gender inequality in STEM education across Sub-Saharan Africa is driven not only by unequal access but also by deep-rooted socio-cultural, economic, and institutional barriers. Although there has been an increase in enrollment in general education, girls remain significantly underrepresented in STEM fields, with an average participation rate of just 21%. Grounded in Crenshaw’s (1989) theory of intersectionality, this literature review examines current academic studies and policy reports from five countries: Cameroon, Kenya, Nigeria, Ghana, and South Africa. The findings identify key barriers like harmful cultural norms, poverty, early marriage, adolescent pregnancy, institutional neglect, and gender-biased curricula. These factors combine to limit girls’ sustained participation and success in STEM education. The review proposes inclusive learning, support for adolescent mothers, curriculum reform, and data-driven policies. It calls for a STEM ecosystem that empowers African girls to become leaders and innovators.